Consumption patterns of drinking water and its impact on public health - Njoku, Anuli; Agbalenyo, Martin (Climate Change, Drinking Water Security, and Public Health: Global Challenges and Solutions, 2026)
Keywords: Consumption (sociology); Globe; Health equity; Investment (military); Population; Population health; Public health; Social determinants of health; Water supply; dept.pch

Racial and Ethnic Disparities in Chronic Stress among Male Caregivers - Unson, Christine; Njoku, Anuli; Bernard, Stanley; Agbalenyo, Martin (International Journal of Environmental Research and Public Health, 2023)
Whereas research on caregiving is well documented, less is known about gender inequalities in caregiver stress, coping mechanisms, and health outcomes, all of which may vary by race, ethnicity, and socioeconomic status. This scoping review investigated racial and ethnic disparities using the Stress Process Model among male caregivers. Several databases were searched including Academic Search Premier, Medline Complete, APA PsycInfo, CINHAL, Google, ProQuest, and Web of Science. Included were peer-reviewed articles in English, published from 1990 to 2022. A total of nine articles fulfilled inclusion criteria. Most of the articles indicated that compared to White male caregivers, African American male caregivers provided more hours of care, assisted with more activities of daily living (ADLs) and instrumental activities of daily living (IADLs), and experienced more financial stress. In terms of coping style, one study found African American male caregivers, compared to White male caregivers, held negative religious beliefs. Another study showed that they were at a higher risk for stroke than their White counterparts. The search revealed a dearth of studies on racial disparities in stress, coping, and health outcomes among male caregivers. Further research is needed on the experiences and perspectives of male minority caregivers. © 2023 by the authors.
Keywords: African American males; aging; caregiver burden; caregiving; coping; dept.pch; health and aging; health disparities; intersectionality; male caregiver; masculinity; older adults; peer-reviewed

Environmental Injustice and Electronic Waste in Ghana: Challenges and Recommendations - Njoku, Anuli; Agbalenyo, Martin; Laude, Janaya; Ajibola, Taiwo Folake; Attah, Mavis Asiwome; Sarko, Samuel Bruce (International Journal of Environmental Research and Public Health, 2023)
Electronic waste (e-waste) or discarded electronic devices that are unwanted, not working, or have reached their end of life pose significant threats to human and environmental health. This is a major concern in Africa, where the majority of e-waste is discarded. In the year 2021, an estimated 57.4 million metric tons of e-waste were generated worldwide. Globally, COVID-19 lockdowns have contributed to increased e-waste generation. Although Africa generates the least of this waste, the continent has been the dumping ground for e-waste from the developed world. The flow of hazardous waste from the prosperous ‘Global North’ to the impoverished ‘Global South’ is termed “toxic colonialism”. Agbogbloshie, Ghana, an e-waste hub where about 39% of e-waste was treated, was listed among the top 10 most polluted places in the world. The discard of e-waste in Ghana presents an issue of environmental injustice, defined as the disproportionate exposure of communities of color and low-income communities to pollution, its associated health and environmental effects, and the unequal environmental protection provided through policies. Despite the economic benefits of e-waste, many civilians (low-income earners, settlers, children, and people with minimal education) are exposed to negative health effects due to poverty, lack of education, and weak regulations. We critically examine the existing literature to gather empirical information on e-waste and environmental injustice. Comprehensive policies and regulations are needed to manage e-waste locally and globally.
Keywords: dept.pch; peer-reviewed

Climate Justice: Access to Safe Drinking Water and Health—A Legal Discourse - Njoku, Anuli U.; Agbalenyo, Martin (Climate Change, Drinking Water Security, and Public Health: Global Challenges and Solutions, 2026)
Addressing the issues of water insecurity and unequal access to water has been a priority of the Sustainable Development Goals. Poor sanitation and inadequate access to drinking water are the second leading causes of death among children worldwide. Access to safe drinking water is a fundamental human right. Climate change represents one of public health’s greatest challenges and significantly exacerbates health disparities. According to the World Health Organization, approximately 3.6 billion people reside in areas highly vulnerable to the effects of climate change. Furthermore, climate change is anticipated to result in roughly 250,000 additional deaths each year between 2030 and 2050. In the United States, climate impacts such as severe storms and floods, escalating wildfires, extreme heat, poor air quality, and diminishing access to food and water disproportionately endanger Black, Brown, and Indigenous communities, low-income groups, people with disabilities, women, children, older adults, and others, making them more susceptible to the harmful health effects of climate change. The formulation and implementation of climate policies are essential to address the negative impacts of climate change. This chapter aims to: (a) describe the effects of climate change on access to safe drinking water; (b) emphasize the implications of climate change on drinking water disparities; (c) highlight policies to mitigate the effects of climate change; and d) discuss recommendations to tackle climate change and inequities in access to water. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2026.
Keywords: Climate change; Environmental injustice; Health disparities; Water disparity; Water injustice; Water insecurities; Water scarcity; dept.pch